PERAN UNITED NATIONS INTERNATIONAL CHILDREN'S EMERGENCY FUND (UNICEF) DALAM MENDUKUNG MANAJEMEN KEBERSIHAN MENSTRUASI (MKM) DI INDIA - Fachrianti, Fika; Fuadi, Ahmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Menstruation in India is often stigmatized, along with inadequate information and access to privacy facilities, this can lead to poor management of menstrual hygiene and privacy as well as discrimination against women, which can threaten the physical, psychological safety, dignity and well-being of teenagers and women in generally. The issue of menstrual health in adolescents and women has become a focus for international regimes such as CRC and CEDAW. This research aims to describe UNICEF's role in supporting India's Menstrual Hygiene Management (MHM). The research method used in this paper uses qualitative research. The research uses a constructivist perspective where the constructivist perspective views ideas and beliefs as having an influence on actions, character and social and political structures. Furthermore, the theory used in this research is international organization theory, in this case international organizations function as arenas, instruments, independent actor in supporting good Menstrual Hygiene Management (MKM) in India. The research results show that UNICEF and its partners are working to change this through promoting awareness regarding menstrual health and hygiene, helping to improve well-being, especially among girls and young women. This collaborative effort uses a variety of methods and initiatives to improve menstrual hygiene.ywords: Role, UNICEF, Menstrual Hygiene Management (MKM), India. keywords: Role, UNICEF, Menstrual Hygiene Management (MKM), India